A RARE ENCOUNTER OF SUPRASELLAR ABSCESS IN A YOUNG WOMAN: A CASE REPORT - V, Melissa; LB, Mohamed Badrulnizam; R, Subashini; A, Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Sellar/suprasellar abscess is a rare entity. We report a case of an immunocompetent young woman with a suprasellar abscess. CASE A 29-year-old female with no known medical illness first presented with worsening headache for 1 year and amenorrhoea since her last childbirth. Her last childbirth was uneventful, which was 4 years prior to that. She breastfed for 3 years but remained amenorrhoeic subsequently. She developed episodes of headache since approximately 2 years postpartum. CT Brain reported a pituitary adenoma, size 1.7x1.7x2.2cm. MRI Brain reported a well-defined suprasellar lesion measuring 2.3x1.8x2.0cm, with homogenous enhancement on post contrast study. MRI conclusion was a pituitary macroadenoma. Her last preoperative hormonal workup was normal except for hypogonadotrophic hypogonadism. As she experienced persistent headache despite no other compressive symptoms i.e. no visual field abnormality, she underwent endoscopic transsphenoidal surgery. Operative finding was of thick pus seen after dura exposed. Post-operative diagnosis was pituitary abscess. There were no symptoms and signs of infection prior to or after surgery. She was treated with 1 week of intravenous antibiotics; cultures were negative. Postoperatively her headache resolved. Tissue histopathological examination revealed mucosal tissue. The initial MRI was then reassessed. An extra pituitary lesion was described, which compresses the pituitary gland inferiorly, with rim enhancement postcontrast. Noted another small lobulated lesion in the right sphenoid sinus with suspicious communication with the extra pituitary lesion. The neuroradiologist’s impression was a suprasellar abscess, possibly ascending infection from sphenoid sinus or an infected hypothalamus/ arachnoid cyst/stalk lesion. CONCLUSION Suprasellar abscesses are even more rarely described compared to sellar abscesses. Intraoperative findings require imaging correlation to confirm the diagnosis, as in this case.